Hybrid deep spatial and statistical feature fusion for accurate MRI brain tumor classification - Iqbal, Saeed; Qureshi, Adnan N.; Alhussein, Musaed; Aurangzeb, Khursheed; Choudhry, Imran Arshad; Anwar, Muhammad Shahid (Frontiers in Computational Neuroscience, 2024)
The classification of medical images is crucial in the biomedical field, and despite attempts to address the issue, significant challenges persist. To effectively categorize medical images, collecting and integrating statistical information that accurately describes the image is essential.This study proposes a unique method for feature extraction that combines deep spatial characteristics with handmade statistical features. The approach involves extracting statistical radiomics features using advanced techniques, followed by a novel handcrafted feature fusion method inspired by the ResNet deep learning model. A new feature fusion framework (FusionNet) is then used to reduce image dimensionality and simplify computation. The proposed approach is tested on MRI images of brain tumors from the BraTS dataset, and the results show that it outperforms existing methods regarding classification accuracy. The study presents three models, including a handcrafted-based model and two CNN models, which completed the binary classification task. The recommended hybrid approach achieved a high F1 score of 96.12±0.41, precision of 97.77±0.32, and accuracy of 97.53±0.24, indicating that it has the potential to serve as a valuable tool for pathologists.